Education leadership Scoping, perspectives and future trajectory - Wolhuter, Charl C. (AOSIS, 2022)
Leadership in education has been demonstrated to make a measurable and significant impact on the success of schools and the achievement levels of learners. This book displays the scope and range of the emerging field of the scholarship of education leadership by means of chapters zooming in on various areas of research in the field. The ensuing chapters focusing on various areas in the field of Education Leadership scholarship are ordered in the following categories: chapters dealing with teacher leadership, school leadership, and mid-level leadership. The sections cover Collective Teacher efficacy in high-performing high schools in South Africa, leadership and leadership challenges of school principals of special schools, entrepreneurial leadership, perceptions of school staff and school governing bodies regarding the use and maintenance of ageing school facilities, and continuous professional development of teachers in Namibia. All the chapters employ a variety of research methods. The research reported on in each of the chapters does not only give clear indications as to how and where to improve practice but also opens vistas for new and future research, suggesting to scholars in the field promising ways to take the field forward with research critical to the continual advance and relevance of the field.